1986
DOI: 10.1002/ana.410190510
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 receptor density remains constant in treated Parkinson's disease

Abstract: D2 dopamine receptor densities were measured in postmortem samples of the caudate nucleus and putamen from 36 parkinsonian patients. The relationship between the age of the patient, duration of the disease, and duration of L-dopa therapy versus density of brain D2 dopamine receptors was examined using [3H]spiperone. Receptor density in parkinsonian tissues was constant over the age range of 56 to 90 years, as was the case for control tissues. Density did not change with duration of disease up to 24 years. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
3

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(31 citation statements)
references
References 27 publications
2
26
0
3
Order By: Relevance
“…A greater than 70% loss of DA innervation to the region is required before D 2 -like receptor number is increased. Although a greater than 90% loss of [ 3 H]mazindol binding to DA terminals occurred in the putamen and greater than 80% losses occurred in the caudate of these (Guttman et al 1986;Pizzolato et al 1995;Rinne et al 1983), other factors may have contributed to the differences in the results. The D2 receptor family includes three subtypes, names D 2 , D 3 , and D 4 , (Sibley et al 1993), which exhibit distinct pharmacological properties and are concentrated in human brain in different regions (Joyce and Meador-Woodruff 1997 (Murray et al 1994); whereas [ 3 H]spiroperidol has low affinity for the D 3 receptor (Sokoloff et al 1990).…”
Section: Discussionmentioning
confidence: 91%
“…A greater than 70% loss of DA innervation to the region is required before D 2 -like receptor number is increased. Although a greater than 90% loss of [ 3 H]mazindol binding to DA terminals occurred in the putamen and greater than 80% losses occurred in the caudate of these (Guttman et al 1986;Pizzolato et al 1995;Rinne et al 1983), other factors may have contributed to the differences in the results. The D2 receptor family includes three subtypes, names D 2 , D 3 , and D 4 , (Sibley et al 1993), which exhibit distinct pharmacological properties and are concentrated in human brain in different regions (Joyce and Meador-Woodruff 1997 (Murray et al 1994); whereas [ 3 H]spiroperidol has low affinity for the D 3 receptor (Sokoloff et al 1990).…”
Section: Discussionmentioning
confidence: 91%
“…The action of L-dopa on supersensitive dopamine receptors in the striatum may lead to greatly increased striatal neuronal activity and, therefore, to hypermetabolic effects. Although denervation results in supersensitivity of dopamine receptors in the striatum, there is some evidence that long-term L-dopa administration can down-regulate dopamine receptors in animals and patients with lesions of the nigrostriatal system (27)(28)(29)(30). Besides the increases in receptor density, however, other adaptive changes involved in the regulation of dopamine release and reuptake also occur following denervation and may contribute to the "overshoot" in cerebral metabolism associated with chronic L-dopa therapy of MPTP-induced parkinsonian monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Although an age-dependent decrease in D2 receptor binding in humans has been reported in a PET study (Wong et al, 1984) and in receptor binding assays (Rinne, 1987;Severson et al, 1982), change was confined to before middle-age, no obvious decrease in D2 receptors being observed in the after 50 years old group. Furthermore, Guttman et al reported that D2 receptor density in parkinsonian tissues is constant over the age range of 56 to 90 years (Guttman et al, 1986). As for the D1 receptor, no change was found during aging in humans in a receptor binding assay (Rinne, 1987).…”
Section: Discussionmentioning
confidence: 97%